Participation in household garbage sorting of Baan Lao Yai community, Kudchum district, Yasothon province - Kim, H.; Singseewo, A.; Sachiyo, M.; Poungsuk, P. (International Journal of Agricultural Technology, 2016)
The sample group in this study consisted of 60 persons obtained by purposive sampling. A structured interview schedule was used for data collection administered with the sample group. Obtained data were analyzed by using the Statistical Package for finding frequency, percentage, mean, and standard deviation. F-test and t-test (independent simple) were also conducted. Results of the study were as follows: Most of the informants (53.33%) were male, 65 years old and above (28.53%), lower secondary school graduates (28.33%), and engaged in agriculture (58.33%). Less than one-half of informants (41.67%) seldom perceived information about garbage sorting. All of informants (100%) perceived the information through social group member and news broadcast tower. Most of them had a high level of knowledge and understanding about garbage ( =3.55) and garbage sorting ( =3.45). The informants participated in household garbage sorting at a high level in 3 aspects:76y 1) coordination in problem solving ( =3.60); 2) coordination in practice ( =4.00); and 3) reduction of an amount of garbages ( =3.71). The informants having the difference in sex, age, frequency in information perception, and a level of knowledge/understanding about garbages had no difference in the participation in household garbage sorting. As a whole, the informants having the difference in educational attainment had a statistically significant difference in the participation in household garbage sorting at .01. Base on its details, there was a statistically significance difference at .01 between educational attainment of the informants and the coordination in problem solving. As a whole, the informants having the difference in a level knowledge and understanding about household garbage sorting had a statistically significance difference at .01 in the participation in household garbage sorting. Based on it details, it was found that the difference in a level of knowledge and understanding about household garbage sorting had statistically significance difference at .01 in the coordination in problem solving.